The accuracy of blood pressure measurement between aneroid and digital sphygmomanometer in reference to mercury sphygmomanometer / Izzah Syahira Mohd - Izzah Syahira , Mohd Ashri (2019)
Accurate measurement is the utmost important thing in an early stage to diagnose a certain disease. Inaccurate measurement can lead to many major health problem such as hypertension. In order to get the most accurate reading, it is important to choose the right devices or monitor to measure the blood pressure of the human. In this research studies, two measuring devices which are the non-mercury equipment were used to compare the reading of the mercury devices where it is claimed to be the most accurate devices in measuring blood pressure. Even though it is the most accurate, this mercury device has the potential of ill effects on health and environment. Thus, this device will be no longer good to use in the future, hence, it has lead to the widespread of the non-mercury sphygmomanometer in the market. The total of 15 subject were tested by using all the three types of the sphygmomanometer and the result were compared to find which has the accurate reading between the two non-mercury used devices in referral to the mercury sphygmomanometer. Based on the research, the findings show the mean difference between mercury sphygmomanometer vs aneroid sphygmomanometer is lesser compared to mercury sphygmomanometer vs digital blood pressure monitor. From one of test result, percentage mean difference for digital devices compared to mercury devices reach 0.1% while for aneroid devices, the results shows lesser than 0.1%. To conclude the findings, based on all three test on aneroid and digital devices, the mean difference from aneroid vs mercury sphygmomanometer shows lesser difference as compared to digital devices which mean the aneroid is the best accurate devices in referral to mercury sphygmomanometer.